Music: A Very Short Introduction - Nicholas Cook (Very short introductions, 2005)
This "Very Short Introduction" to music invites us to really think about music and the values and qualities we ascribe to it. Drawing on a range of examples from Beethoven to the Spice Girls to Chinese zither music, Nicholas Cook attempts to provide a framework for thinking about all music.